Feeding preference and growth response of early adults abalone, Haliotis squamata on some macroalgae - Deny Suhernawan Yusup; MAHARDIKA I GEDE; SUARNA I WAYAN; GIRI I NYOMAN ADIASMARA (Society for Indonesian Biodiversity, 2020)
Abstract. Yusup DS, Mahardika IG, Suarna IW, Giri INA. 2020. Feeding preference and growth response of early adults abalone, Haliotis squamata on some macroalgae. Biodiversitas 21: 4369-4375. Study on early adult Haliotis squamata fresh feed has evaluated some macroalgae, however, a study on Enteromorpha sp., Halymenia sp., and Hypnea sp. have not been carried out. This study was proposed to evaluate the feeding preference (feed response and feed intake) and the growth performance of early adult H. squamata on some macroalgae. Seven species of macroalgae were evaluated as unpair feeding choice and the experiment design employed was completely randomized design. The results showed that H. squamata responded variously to the seven macroalgae species and the food deprivation (fasting) data showed mounting response to all macroalgae. Ulva lactuca and Enteromorpha sp. were the most responded which up to four times higher compared to the least responded i.e. Halymenia sp. and Sargassum sp. The highest to the lowest palatable feed intake (FI) were Gracillaria sp, Eucheuma spinosum, Ulva lactuca, Halymenia sp., Enteromorpha sp., Sargassum sp. and Hypnea sp. respectively. The first four palatable macroalgae resulted in various growth responses of H. squamata. Except for Halymenia sp., the feed intake (FI) rate showed an opposite linear correlation to growth response and FCR. The daily growth rate (g/day) was Ulva lactuca (0.104), Enteropmorpha sp. (0.085), Gracillaria sp. (0.084), and Halymenia sp. (0.016).